Medical Imaging Devices: Current Technologies and Future Trends - Tariq, Tariq Abdullah; Razzaq, Salam Adel Abdel; Wahab, Sara Wisam; Kazem, Ahmed Saleh; Kazem, Reda Ghanem (American Journal of Biodiversity, 2025)
The role of medical imaging modalities in modern healthcare: An overview. Medical imaging modalities are crucial in the diagnosis, management, and treatment of diseases in modern healthcare. Medical imaging non-invasively visualizes internal structures and functions of the body, enabling numerous tasks, including the early detection and management of diseases, monitoring of treatment outcomes, guidance in medical procedures, and drug delivery. Various medical imaging modalities, such as X-ray imaging, computed tomography (CT), magnetic resonance imaging (MRI), ultrasonography (US), nuclear medicine imaging, and cardiovascular imaging, have been developed with different physical principles and clinical applications. Nowadays, most medical imaging modalities are digitally performed, and digital imaging results are stored and transmitted, providing easy access to data. In addition, newly emerging technologies, such as computational and artificial intelligence (AI), further improve medical imaging practice. AI can assist medical experts by rapidly processing and analyzing large amounts of medical imaging data. AI algorithms can identify and detect patterns, predict disease onset, and propose the optimum treatment plan. Therefore, AI implementation may revolutionize medical imaging and greatly improve healthcare. Medical imaging is broadly defined as the non-invasive visualization, representation, and analysis of internal structures and functions of the body . The visual representations are called medical images or images; these are stored in the digital format and managed by Picture Archiving and Communication System (PACS). The health professionals skilled in interpreting medical images are called radiographers. While the field of medical imaging encompasses a wide range of applications and technologies, it is traditionally divided into modalities. Each modality has its physical principles and is suitable for different clinical tasks. A great deal of research and development focuses on generating more sophisticated imaging equipment, new contrast media, and analytical methods to improve the diagnostic capabilities of already existing imaging devices. Of course, much attention is also drawn to completely new imaging capabilities.